Incorporation of 7-dehydrocholesterol into liposomes as a simple, universal and efficient way to enhance anticancer activity by combining PDT and photoactivated chemotherapy. Issue 93 (7th November 2019) - Wang, Youchao; Tian, Nana; Li, Chao; Hou, Yuanjun; Wang, Xuesong; Zhou, Qianxiong
Abstract : Incorporation of 7-dehydrocholesterol instead of cholesterol can efficiently enhance the anticancer activity of photosensitizer-encapsulated liposomes upon irradiation. Abstract : Cholesterol (CHOL) is an indispensable component of liposomes. Incorporation of 7-dehydrocholesterol (7-DHC) instead of CHOL can efficiently enhance the anticancer activity of photosensitizer-encapsulated liposomes upon irradiation, yielding an IC50 value about half of that of CHOL-based controls. The photo-oxidation of 7-DHC into its endoperoxide form by singlet oxygen may account for the enhanced therapeutic effect, realizing an efficient combination of photodynamic therapy (PDT) and photoactivated chemotherapy.